Development of Reagents to detect markers of Hepatitis B virus infection - Fernando, C. R. S. (Faculty of Medicine: University of Colombo, 1992)
The development of enzyme linked immunosorbent assays for detecting hepatitis B surface antigen and antibodies, the development of a latex agglutination test for detecting hepatitis B; amd a study on the prevalence of markers of hepatitis B virus infection in diabetics on regular insulin therapy at a Government hospital clinic are reported.
Keywords: Hepatitis B Virus-diagnosis; Hepatitis B Virus-diagnosis purification; Hepatitis B Antibodies; Hepatitis B Surface Antigens